What is integrated care?. (December 2014) - Huang, Heather; Meller, William; Kishi, Yasuhiro; Kathol, Roger G.
Abstract Increasing awareness of mental illness's impact on medical and psychiatric health has accelerated global efforts to integrate medical and behavioural health services. As the field of integration has advanced, numerous integrated programmes have been implemented. In examining the impact of these programmes, it is important to maintain a standardized vocabulary to describe the various components of their integration. Additionally important is examination of how these programmes impact elements of patient care and the healthcare system. Specifically, what value do they bring? This article will discuss the importance of carefully assessing the value integrated services bring to patients, and questioning whether they do so in ways in which today's segregated world of medical and behavioural health cannot. This article will also explore the various settings in which medical and behavioural integration can bring added value.